2021
DOI: 10.12998/wjcc.v9.i21.5754
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for hepatocellular carcinoma with extrahepatic metastasis

Abstract: Extrahepatic metastasis (EHM) of hepatocellular carcinoma (HCC) has increasingly been seen due to improved survival with effective management of intrahepatic lesions. The presence of EHM indicates an advanced stage of HCC, for which systemic therapy serves as the standard treatment modality. Since the approval of Sorafenib as the first systemic agent in 2007, it took almost a decade to show its efficacy in both first and further lines of setting until the landscape of systemic drugs was finally expanded. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Immunotherapy, particularly anti-PD-1/PD-L1 and anti-CTLA-4 antibodies, has shown promise as a treatment for advanced HCC in recent years ( 27 ). It has been a breakthrough in anti-cancer therapy and has completely revolutionized treatment strategies.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…Immunotherapy, particularly anti-PD-1/PD-L1 and anti-CTLA-4 antibodies, has shown promise as a treatment for advanced HCC in recent years ( 27 ). It has been a breakthrough in anti-cancer therapy and has completely revolutionized treatment strategies.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“… 3 , 4 Previous studies reported that HCC with EHM had obviously poorer outcome than those without EHM. 4 , 5 Data has proven that HCC with EHM, the expected median survival was 6–8 months. 5 The lungs are the most common organ for extrahepatic spread, but most metastases are multifocal and often unsuitable for curable therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Data has proven that HCC with EHM, the expected median survival was 6–8 months. 5 The lungs are the most common organ for extrahepatic spread, but most metastases are multifocal and often unsuitable for curable therapy. Thus, the clinical conclusion and prognosis of patients with EHM usually administered with system therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical treatment and diagnosis of HCC patients have considerably improved in the last few years, the prognosis for patients with HCC, who also have DOI: 10.14218/CSP.2022.00006 | Volume 00 Issue 00, Month Year 2 Dummy Running Header (Right) Cancer Screen Prev distant metastases (DM), remains dismal. 4 As a result, predicting models for estimating DM in HCC patients and the prognosis of HCC patients with DM are required. Numerous risk factors and prognostic variables have been identified in prior studies, such as higher T stage, surgery, tumor size, etc.…”
Section: Introductionmentioning
confidence: 99%